Heat‐shock transcription factor 1 is critically involved in the ischaemia‐induced cardiac hypertrophy via JAK2/STAT3 pathway. Issue 9 (11th July 2018) - Yuan, Lingyan; Qiu, Lin; Ye, Yong; Wu, Jian; Wang, Shuchun; Wang, Xingxu; Zhou, Ning; Zou, Yunzeng
Abstract: Cardiac hypertrophy after myocardial infarction (MI) is an independent risk factor for heart failure. Regression of cardiac hypertrophy has emerged as a promising strategy in the treatment of MI patients. Here, we have been suggested that heat‐shock transcription factor 1 (HSF1) is a novel repressor of ischaemia‐induced cardiac hypertrophy. Ligation of left anterior descending coronary was used to produce MI in HSF1‐deficient heterozygote (KO), HSF1 transgenic (TG) mice and their wild‐type (WT) littermates, respectively. Neonatal rat cardiomyocytes (NRCMs) were treated by hypoxia to mimic MI in vitro. The HSF1 phosphorylation was significantly reduced in the infarct border zone of mouse left ventricles (LVs) 1 week after MI and in the hypoxia‐treated NRCMs. HSF1 KO mice showed more significant maladaptive cardiac hypertrophy and deteriorated cardiac dysfunction 1 week after MI compared to WT MI mice. Deficiency of HSF1 by siRNA transfection notably increased the hypoxia‐induced myocardial hypertrophy in NRCMs. Mechanistically, Janus kinase 2 (JAK2) and its effector, signal transducer and activator of transcription 3 (STAT3) were found to be significantly increased in the LV infarct border zone of WT mice after MI as well as the NRCMs treated by hypoxia. These alterations were more significant in HSF1 KO mice and NRCMs transfected with HSF1 SiRNA. Inversely, HSF1 TG mice showed significantly ameliorated cardiac hypertrophy and heart failure 1 week after LAD ligation compared to their WT littermates. Our data collectively demonstrated that HSF1 is critically involved in the pathological cardiac hypertrophy after MI via modulating JAK2/STAT3 signalling and may constitute a potential therapeutic target for MI patients.